Central questions of philosophy - "Ayer, A.J." (Middlesex, 1982)
This book is more strictly philosophical. It begins with an attempt to explain what philosophy is and after a few historical comments goes on to give examples which illustrate the special character of metaphysical arguments.
Keywords: Knowledge theory of philosophy